Role Of Doppler Ultrasound In Pre-Eclampsia And Its Perinatal Outcome (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background: The main purpose of providing antenatal care is to identify women at risk of complications as a result of impaired uteroplacental circulation such as pre-eclampsia.Aim: To describe practical application of Doppler ultrasound in obstetrics with analysis of blood flow velocity waveform in pre-eclampsia and to examine perinatal outcome in pregnancies with altered Doppler indices. Material and Method: This is a prospective study of 40 pregnant women with pre-eclampsia evaluated sono-graphically with color Doppler and to be followed subsequently for any adverse perinatal outcome. Result: Out of 40 cases 45% of cases were found in 25-29 years age group. 25 cases had abnormal uterine artery Doppler indices accounting for 62.5%, while 15 cases had a normal doppler indices accounting for 37.5%. Out of 40 cases, 24 cases had abnormal Middle cerebral artery accounting for 60%. In our study 14 cases had abnormal umbilical artery Doppler indices accounting for 35%, while 26 cases had a normal Doppler index accounting for 65%. In this study total 6 cases (15%) of perinatal mortality were seen. Conclusion: The knowledge of Doppler arteries waveform may help to improve pregnancy outcome and any permit identification and assessment of pre-eclampsia at earliest gestational age as compared to other ante partum test modalities.
Keywords: Preeclampsia; Pregnancy; Doppler ultrasound; Gestational age; Perinatal Outcome